Immune regulation and blood–brain barrier permeability in cerebral small vessel disease: study protocol of the INflammation and Small Vessel Disease (INSVD) study – a multicentre prospective cohort study - Roy P C Kessels; Audrey Low; Hugh Markus; Anil Tuladhar; Frank‐Erik de Leeuw; Robin G Morris; Ziad Mallat; Niels P Riksen; Daniel J Tozer; Sanne van Winden; Lupei Cai; Marnix C Maas; et al. (BMJ Open, 2024)
Introduction The INflammation and Small Vessel Disease (INSVD) study aims to investigate whether peripheral inflammation, immune (dys)regulation and blood–brain barrier (BBB) permeability relate to disease progression in cerebral small vessel disease (SVD). This research aims to pinpoint specific components of the immune response in SVD relating to disease progression. This could identify biomarkers of SVD progression, as well as potential therapeutic targets to inform the development and repurposing of drugs to reduce or prevent SVD, cognitive decline and vascular dementia.Methods and analysis INSVD is a prospective observational multicentre cohort study in individuals with symptomatic SVD. This longitudinal study combines comprehensive immunophenotyping of the peripheral blood immune compartment with advanced neuroimaging markers of SVD and BBB permeability. The main SVD marker of interest is white matter microstructure as determined by diffusion tensor imaging, a valuable marker of disease progression owing to its sensitivity to early alterations to white matter integrity. The research is being conducted in two sites—in the UK (Cambridge) and the Netherlands (Nijmegen)—with each site recruiting 100 participants (total n=200). Participants undergo clinical and cognitive assessments, blood draws, and brain MRI at baseline and 2-year follow-up.Ethics and dissemination This study received ethical approval from the local ethics boards (UK: East of England—Cambridge Central Research Ethics Committee (REC) ref: 22/EE/00141, Integrated Research Application System (IRAS) ID: 312 747. Netherlands: Medical Research Ethics Committee (MREC) Oost-Nederland, ref: 2022-13623, NL-number: NL80258.091.22). Written informed consent was obtained from all subjects before the study. Any participant-derived benefits resulting from this research, such as new insights into disease mechanisms or possible novel therapies, will be disseminated to study participants, patient groups and members of the public.Trial registration number NCT05746221.